Influence of elementary homemaking education upon ninth-grade enrollment in Arizona - Burton, Byrd, author; Morgan, David H., advisor; Williamson, Maude, committee member; Elliff, Rowan E., committee member; Marshall, Thomas O., committee member; Holman, Mary V., committee member (Colorado State University. Libraries, 1943)
To view the abstract, please see the full text of the document.
Keywords: Home economics -- Study and teaching; Home economics -- Arizona